EFFECTIVENESS OF DISCOVERY LEARNING MODEL ON STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITY - Nur, Fitriani; Tayeb, Thamrin; Widayanti, Virginia Meyka; Sriyanti, A.; Nurhidayah, Nurhidayah (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract: This study aims to determine the application of discovery learning model on students' mathematical problem solving abilities. This research is experimental research with a quasi experimental design. The population in this study were all students of grade VII SMPN 4 Sungguminasa with grade VII.A as samples an experimental class and grade VII.C as a control class. The research instruments used a test to solve mathematical problems. Data analysis techniques were descriptive statistical analysis and inferential statistical analysis. Based on the results of the analysis, it was found that the application of discovery learning model is effective on students' mathematical problem solving abilities. Abstrak: Penelitian ini bertujuan untuk mengetahui penerapan model pembelajaran discovery learning terhadap kemampuan pemecahan masalah matematika siswa. Penelitian ini merupakan jenis penelitian eksperimen dengan desain penelitian yaitu quasi eksperimental design. Populasi pada penelitian ini yaitu seluruh siswa kelas VII SMPN 4 Sungguminasa dengan sampel pada kelas VII.A sebagai kelas eksperimen dan kelas VII.C sebagai kelas kontrol. Instrumen dalam penelitian ini adalah tes kemampuan pemecahan masalah matematika. Teknik analisis data menggunakan analisis statistik deskriptif dan analisis statistik inferensial. Berdasarkan hasil analisis diperoleh bahwa penerapan model pembelajaran discovery learning efektif terhadap kemampuan pemecahan masalah matematika siswa.